The Compounding Pain of Familial Betrayal and Institutional Failure in Nigerian Rape Narratives - AWOGU-MADUAGUW , Edith Abisola; LOKO , Olufunmilayo Janet; OMESU, Modupeoluwa Osariehienagha (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This article examines the representation of rape in Nigerian literature, a topic often shrouded in cultural silence and stigma. It argues that selected Nigerian novels provide a crucial platform for exposing the compounded pain of sexual violence, a pain intensified by familial betrayal and institutional failure. Drawing on transactional reader-response theory, this qualitative study analyses Yejide Kilanko’s Daughters Who Walk This Path and Nnedi Okorafor’s Who Fears Death to explore how cultural norms perpetuate the suffering of rape victims. Using close reading as an analytical tool, the study examines how characterisation, plot, and literary devices depict the psychological aftermath of rape. The transactional reader-response theory is applied to understand the dynamic interaction between the text and the reader's interpretation of these traumatic experiences. The findings reveal that victims often endure self-blame, isolation, and a lack of institutional, with priorities like family honour aggravating their trauma. This research emphasises literature’s critical role in challenging harmful norms and fostering empathy, recommending awareness campaigns, policy reforms and community based initiatives to protect survivors and prevent further harm.